Essays on the economic impact of religiosity and family ties - Ji, Yaling (2019)
This thesis seeks an understanding of how cultural factors may affect economic behavior and drive aggregate outcomes. It comprises 3 self-contained essays that explore the link between the strength of social institutions and economic issues, with the purpose of providing insights from an empirical angle to yield policy-relevant research outcomes. We focus on the dominance of two social institutions in this thesis – religion and family, both of which are historically common foundations of human cultures throughout the world. We investigate how variations in the level of religiosity and the strength of family ties may affect attitudes towards immigration, as well as the extent of financial inclusiveness.